Logiczna analiza wypowiedzi dotyczących braku pozytywnych i negatywnych odpowiedzi - Lapis, Włodzimierz (Investigationes Linguisticae, 2007)
Ninety-nine statements concerning the lack of positive or negative reply were gathered from Polish Internet sites in this article and they were analysed in terms of their logical meaning (whether they denoted acceptance or lack of it). We also analysed in which situations we are dealing with such coincidences and what exactly is the touchstone that enables us to take this classification decision.